Evaluation of Inhibin B and Lipid Profile Levels in Secondary Infertile Women - Ali_Samarrai, Nuha Ali Hadi; Zanzal, Rana Raad; Wasmi, Mays Subhi (American Journal of Bioscience and Clinical Integrity, 2025)
Ninety blood samples were collected from infertile and healthy women, aged 19 to 41, between October 15, 2022, and January 15, 2023, for the present study. Thirty samples of healthy women served as the control group, whereas sixty samples of infertile women made up the first group (G1). Lipids (cholesterol, triglycerides, high-density lipoprotein, low-density lipoprotein, and very low-density lipoprotein) and inhibin B hormone levels were assessed from the samples taken for this investigation. The findings of the present investigation. Chemistry lab tests: This study’s findings suggest that. There were no statistically significant changes between G1 and G2 in the reduction of inhibin B levels in infertile women (P0.05) when comparing to the control group. Also There was no statistically significant difference between G1 and G2 in terms of blood cholesterol levels when compared to the healthy controls (P0.05). and At the level of probability (P0.05), there was a statistically significant rise in triglycerides in the blood serum of both G1 and G2 compared to the healthy group. also Both G1 and G2 had lower levels of high-density lipoprotein in their blood serum than the healthy controls, at a probability level (P0.05), with no discernible difference between the two groups. There was no statistically significant difference between G1 and G2 with respect to the elevated levels of low-density lipoprotein and very low-density lipoprotein in their blood serum when compared to the healthy control group (P0.05).